A 16-week rugby training program improves power and change of direction speed in talented girls. (3rd July 2022) - Müller, Camila Borges; da Veiga, Rousseau Silva; da Silva, Amanda Franco; Wilhelm, Eurico Nestor; Teixeira Vaz, Luís Miguel; Bergmann, Gabriel Gustavo; dos Santos Pinheiro, Eraldo
ABSTRACT: Rugby Sevens has been extensively investigated in elite athletes, but talented teenagers require more attention from sports development researchers. This study aimed to investigate a 16-week intervention of rugby training on physical performance in talented girls. Fifteen girls (14.00 ± 0.53 years, 156.27 ± 4.03 cm, 52.53 ± 5.67 kg) selected as physically talented for rugby to participate in a sport-development program were divided into two groups. The intervention group (IG) carried out two-session per week of rugby training for 16 weeks. The control group (CG) did not perform any type of physical training. A battery of physical tests was carried out before and after the intervention. A two-way ANOVA with group*time was carried out for analysis. Both groups increased their performance in countermovement jump, handgrip isometric strength, linear sprints, and 5-m multiple shuttle test (p < 0.05). However, squat jump, change of direction speed (CODS), and running anaerobic sprint test improved in IG (p < 0.05), while no difference was found in the CG. These results suggest that variables related to power output and CODS may be improved with the rugby training due to the specificity of the modality in talented girls.